ChemInform Abstract: 2, 3‐Dihalo‐1‐propenes as Building Blocks in Cu(I)‐Catalyzed Domino Reactions: Efficient and Selective Synthesis of Furans. Issue 12 (March 2015) - Schmidt, Dietmar; Malakar, Chandi C.; Beifuss, Uwe
Abstract Trisubstituted furans are synthesized in an efficient and selective one‐pot process by reacting dibromopropenes with 1, 3‐dicarbonyl compounds.